Strandberg-type polyoxometalate deriving O, P co-doped NiMoS/CC catalyst for highly efficient hydrogen evolution electrocatalysis. (19th July 2022) - Sun, Fengyue; Yang, Lingyu; Yue, Changle; Liu, Yang; Bao, Wenjing; Tuo, Yongxiao; Feng, Xiang; Lu, Yukun
Abstract: Hydrogen production from electrolytic water is an indispensable component in the field of renewable energy. The preparation of electrocatalysts with low price and high performance is essential for hydrogen evolution reaction (HER). Herein, Strandberg-type polyoxometalate was used as pre-assembled molecular platforms to construct and regulate NiMoS active sites at the atomic level. O, P doping was performed to boost the number of active sites using controllable sulfidation method. O, P–NiMoS nanoparticles supported on highly conductive carbon cloth exhibit significant activity for HER. The overpotential are only 39 and 30 mV at a current density of 10 mA cm −2 in both acidic and alkaline solutions, respectively. This excellent performance can be attributed to the finely tailored NiMoS active sites, increase of S-unsaturated species and the synergistic effect between carbon cloth and O, P–NiMoS. Therefore, this study provides a feasible strategy for rational design of efficient electrocatalysts for renewable energy applications. Graphical abstract: Image 1 Highlights: POMs as pre-assembling platform for modulating NiMoS active sites at atomic level. O and P doping forms abundant S-unsaturated species serving as active sites. NiMoS/CC shows excellent HER catalytic performance in acidic and basic solutions.